The demagogical limits of the political discourse - Cornutiu, Gavril (Advances in Social Sciences Research Journal, 2015)
Starting from the rising mass violence potential and increased terrorism în Europe, a short analysis from a scientific point of view of the consequences of increased emigration to Europe was made. The officials refuse any sincere dialogue on the topic due to political corectness obedience. The conclusion is that only free debate at all levels of society can lead to just conclusions which în turn can help avoid blood shed în the future of Europe.